Medicinal plant diversity and conservation status assessment in Sapen forest, East Java - Ainiyah, Roisatul; Nugroho , Endik Deni; Ardiansyah , Reza; Fathurrohman, Amang; Ahwan , Zainul; Dayat , Muhammad; Wibisono, Mulyono (Biology Education Department, Universitas Insan Budi Utomo, Malang, Indonesia, 2026)
Sapen Forest harbors high plant diversity, yet information on its medicinal plant resources and their conservation status has remained limited. This study aims to document medicinal plant diversity and evaluate its conservation status in Sapen Forest, East Java, Indonesia. Field surveys were conducted in 2021 within a 5-ha area using 36 systematically established sampling plots. Medicinal plant species were inventoried, vegetation structure was analyzed using the Importance Value Index (IVI), and conservation status was evaluated according to the International Union for Conservation of Nature (IUCN) Red List. Species were identified to the species level, and their traditional medicinal uses were compiled from published literature. A total of 68 medicinal plant species belonging to 38 families were recorded. Ageratina riparia exhibited the highest IVI (23.20), followed by Alternanthera sessilis (20.82) and Synedrella nodiflora (14.68). The Shannon–Wiener diversity index (H') was 3.05, indicating high medicinal plant diversity. Most species were classified as Not Evaluated (NE), while five species were categorized as Least Concern (LC) and one cultivated species, Brugmansia suaveolens, as Extinct in the Wild (EW). These findings demonstrate that Sapen Forest is an important reservoir of medicinal plant diversity and provides baseline information to support biodiversity conservation and the sustainable management of medicinal plant resources.